Bridging the gap: The future of biosimilars regulations - Anan S. Jarab; Shrouq R Abu Heshmeh; Ahmad Z. Al Meslamani (Taylor & Francis Group, 2024)
Biosimilar vaccines and immunotherapeutic are innovative approaches in medical research. This commentary addresses the current disparities in regulations of biosimilar vaccines and immunotherapeutic products across different nations. It also navigates the benefits of global regulatory alignment and challenges that may be encountered. The current discrepancies in regulations across different countries, which pose significant challenges for the development and approval of biosimilar vaccines and immunotherapeutic products. These disparities often lead to delayed market access, increased development costs, and hindered innovation. The commentary stresses that such obstacles could be mitigated through harmonized regulations, resulting in faster approvals, reduced healthcare costs, and improved patient outcomes. Moreover, the commentary explores the specific complexities associated with biosimilar vaccines and immunotherapeutic, such as the intricate evaluation of biosimilarity due to their molecular composition and immunogenic properties. In conclusion, the editorial advocates for collaborative efforts to overcome the challenges in achieving global regulatory harmonization for biosimilars. This includes establishing uniform standards, fostering international cooperation among regulatory agencies, and promoting educational initiatives for healthcare providers and regulators. The ultimate goal is to ensure that patients worldwide have timely access to safe, effective, and affordable biosimilar treatments.